2021
DOI: 10.1186/s41235-021-00286-1
|View full text |Cite
|
Sign up to set email alerts
|

Great expectations: minor differences in initial instructions have a major impact on visual search in the absence of feedback

Abstract: Professions such as radiology and aviation security screening that rely on visual search—the act of looking for targets among distractors—often cannot provide operators immediate feedback, which can create situations where performance may be largely driven by the searchers’ own expectations. For example, if searchers do not expect relatively hard-to-spot targets to be present in a given search, they may find easy-to-spot targets but systematically quit searching before finding more difficult ones. Without feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The hypothesis that participants who received eyewitness instructions would have higher discriminability than participants who received non-specific instructions was not supported. Thus, it seems that the effects of instructions on attention (Varakin & Hale, 2014 ), encoding strategy (Coin & Tiberghien, 1997 ; Craik & Tulving, 1975 ), or metacognition (Cox et al, 2021 ; Mazzoni & Nelson, 1995 ) seen in more basic work did not extend to this eyewitness identification paradigm. This finding is in line with those of Yarmey ( 2004 ), but contrasts findings of increased eyewitness identification accuracy when participants were warned of an upcoming crime or lineup (Cowan et al, 2014 ; Lindsay et al, 1998 ; Wulff & Hyman, 2022 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The hypothesis that participants who received eyewitness instructions would have higher discriminability than participants who received non-specific instructions was not supported. Thus, it seems that the effects of instructions on attention (Varakin & Hale, 2014 ), encoding strategy (Coin & Tiberghien, 1997 ; Craik & Tulving, 1975 ), or metacognition (Cox et al, 2021 ; Mazzoni & Nelson, 1995 ) seen in more basic work did not extend to this eyewitness identification paradigm. This finding is in line with those of Yarmey ( 2004 ), but contrasts findings of increased eyewitness identification accuracy when participants were warned of an upcoming crime or lineup (Cowan et al, 2014 ; Lindsay et al, 1998 ; Wulff & Hyman, 2022 ).…”
Section: Discussionmentioning
confidence: 84%
“…For example, judgments of learning varied depending on whether participants received incidental or intentional encoding instructions (Mazzoni & Nelson, 1995 ). Cox et al ( 2021 ) found that instructions changed performance in a lower-level visual search task, which they hypothesized was due to a change of expectation of target frequency. To bridge the gap between basic and applied research, Shapiro and Penrod ( 1986 ) meta-analyzed 128 face memory studies, 20% of which were eyewitness identification studies.…”
Section: Introductionmentioning
confidence: 99%
“…Schwark et al ( 2012 ) found that they could reduce miss errors in a search task by falsely telling observers that they had missed targets. Cox et al ( 2021 ) were able to produce different error rates and criteria by telling observers at the start of a trial either that a display contained "up to two" or "one or two" targets. Observers made more errors with the "up to two targets" instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed activation account updates throughout a task according to three factors: a selection-based reinforcement that boosts activation for recently found targets, a reinforcement of the categorical structure through a relative activation boost to all category members in proportion to their representativeness (which serves to reinforce the instructionally-defined search template that remains active throughout the task; Cox et al, 2021), and a small decay in activation for non-selected targets. Crucially, the decay for non-selected targets becomes mitigated by the categorical reinforcement, such that the activation nodes of highlyrepresentative targets decay slower than poorly-representative ones.…”
Section: Discussionmentioning
confidence: 99%
“…As an individual engages in the search task, however, the experience of finding specific target types biases their attentional set towards recently selected target types, allowing for swifter and easier subsequent selections (Clark et al, 2015). Two additional factors update the observer's attentional set, a small decay in activation for targets not found on each trial, which causes the low prevalence cost, but also a reinforcement for all targets within the categorical search set proportional to its representativeness any time a category member is found (because observers do not forget their initial instructions; Cox et al, 2021). This last input, visualized in Figure 1 through the variably sized light green arrows, helps to anchor the attentional bias towards highly-representative items even if they are contextually rare.…”
mentioning
confidence: 99%